Intraoperative Indocyanine Green Retention Test of Left Hemiliver in Decision-Making for Patients With Hepatocellular Carcinoma Undergoing Right Hepatectomy - Yu, Tingdong; Ye, Xinping; Wen, Zhang; Zhu, Guangzhi; Su, Hao; Han, Chuangye; Huang, Ketuan; Qin, Wei; Liao, Xiwen; Yang, Chengkun; Liu, Zhen; Wang, Xiangkun; et al. (Frontiers in Surgery, 2021)
Introduction: The aim of this study was to select qualified patients with hepatocellular carcinoma (HCC) to underwent right hepatectomy (RH) via intraoperative indocyanine green retention test at 15 minutes (ICG-R15) of left hemiliver, which prevent severe post-hepatectomy liver failure (PHLF). Methods: Twenty HCC patients who were preoperatively planned to undergo RH were enrolled. Intraoperative ICG-R15 of left hemiliver was measured after the right Glissonean pedicle was completely blocked. Patients then underwent RH when intraoperative ICG-R15 was ≤ 10%. Otherwise, patients underwent staged RH (SRH), either associating liver partitioning and portal vein ligation for staged hepatectomy (ALPPS) or portal vein ligation (PVL) followed by staged-2 RH. The comparison group consisted of patients with a ratio of standard left liver volume (SLLV) of > 40% and preoperative ICG-R15  10% who underwent RH. The clinical outcomes of these two groups were compared. Results: Of 20 patients, 6 underwent 1-stage RH, 6 underwent ALPPS and 5 underwent PVL followed by stage-2 RH, and 3 failed to proceed to stage-2 RH after PVL. No significant differences were found among the 17 patients who underwent 1- or 2-stage RH in the study group, the 19 patients in the comparison group, the 11 patients in the 2-stage RH group and the 6 patients in the 1-stage RH group in incidences of PHLF, post-operative complications, hospital stay and HCC recurrence within 1 year after RH. Compared with the staged-1 ALPPS group, the mean operative time and blood loss of the staged-1 PVL group were significantly less (p < 0.001 and p = 0.022, respectively). The staged-1 PVL group had a significantly longer waiting-time (43.4 vs. 14.0 days, p = 0.016) than the staged-1 ALPPS group to proceed to staged-2 RH. After staged-2 RH, tumor recurrence within 1 year was 20% (1/5) in patients after PVL and 50% (3/6) after staged-1 ALPPS. Conclusions: Intraoperative ICG-R15 ≤ 10% of left hemiliver was valuable in intraoperative decision-making for patients who were planned to undergo RH. There is a possibility that staged-1 PVL might help to select patients with more favorable biological behavior to undergo staged-2 RH.